The Headmaster’s Strategy to Improve Civil Servants’ Work Performance (Administration Department) in Pringgasela High School, East Lombok-NTB - Parhan, Parhan (FIA UB, 2021)
This study aims to determine the headmaster's strategy to improve the work performance of Civil servant [administration department] at Pringgasela Senior High School. This research used the descriptive qualitative research method. The data in this study were obtained from interviews with informants and documentation. The data analysis was carried out in the following steps: data collection, data reduction, data presentation and drawing conclusions or verification (Miles and Huberman, 2014: 20). The results of this study stated that the headmaster's strategy to improve the work performance of civil servants in the administration department: Making disciplinary rules about working hours that must be on time. Building a spirit of togetherness through civil servants’ friends, superiors and subordinates, as well as communication, intimacy and mutual respect. Providing role models for all civil servants. The results of the headmaster's strategy show the work performance of civil servants [administration department] is classified good in providing services, however they have not provided satisfaction to: teachers, students or other related parties. As for the constraints faced when performing performance in providing services, by the Administrative Apparatus such as the lack of responsiveness of the Administrative Apparatus in understanding consumer psychology, the large amount of workload that is carried out in a little bit of time and the supporting infrastructure is inadequate and lack of personel.